Patients with type 2 diabetes have reduced levels of plasma vitamin D3 and are well correlated with the oxidative stress parameters - Saha, Pinaki; Dasgupta, Sayantan; Sen, Santanu; Kumar, Arun; Biswas, Utpal Kumar (Asian Journal of Medical Sciences, 2016)
Background: Diabetes has emerged as an epidemic in this country as well as worldwide. Increased oxidative stress and decreased antioxidant defense are established etiological factors of this multifactorial disease. Some of the recent studies reported deficiency of vitamin-D3 in type-2 diabetic patients. Aims and Objectives: This study was aimed to estimate the total oxidative stress (TOS), the total antioxidant defense (TAD) and the plasma 25-hydroxy vitamin D3 levels in patients of type-2 diabetes patients with an objective to elucidate if there is any significant correlation between the TOS, TAD and vitamin D3 levels. Materials and Methods: The study was conducted in forty patients recently diagnosed type-2 diabetic and the findings were compared with age/sex matched healthy controls. Total oxidative stress and TAD values was estimated by two simple colorimetric tests developed and standardized in our laboratory, plasma 25-hydroxy vitamin D3 by standardized ELISA method. Results and Discussion: The levels of vitamin D3 in patients was found to be 50.17 ± 15.85ng/ml which was significantly decreased (P<0.001) when compared to healthy control group (75.42 ± 9.59 ng/ml). The plasma vitamin D3 levels show a significant positive correlation (r=0.564, P<0.001) with the TAD values and a significant negative correlation (r=-0.561, P<0.001) with the TOS values in the study subjects. There is significant positive correlation of 25-OH vitamin-D3 with antioxidant defense and significant negative correlation with oxidative stress observed in the current study, and the levels of vitamin D3 were significantly decreased in type-2 diabetes when compared to the healthy controls. Conclusion: The type-2 diabetes patients are usually associated with vitamin D3 deficiency which is significantly correlated with the oxidative stress conditions in this group of patients. Asian Journal of Medical Sciences Vol. 7(3) 2016 35-40